Anterior pelvic tilt in elite cyclists: A comparative matched pairs study - Upton, K.; Everett, S. (1999)
A fundamental factor affecting cycling performance is the position the cyclist assumes on the bike. Central to an optimal aerodynamic cyclist position is the contribution of anterior pelvic tilt to lumbopelvic-hip flexion. Physiotherapists in South Australia screen competitive track cyclists to measure their degree of anterior pelvic tilt, with the view to maximise this characteristic. However, this screening test is of limited value as anterior pelvic tilt has not yet been established as a sport specific quality of track cyclists. Few prospective studies have investigated whether or not a difference exists between anterior pelvic tilt in elite cyclists and non-cyclists. This study was undertaken to measure and compare the values of anterior pelvic tilt in a group of elite cyclists with that of a group of age, gender and race matched non-cyclists. An observational, cross-sectional, comparative, parallel groups study was used to investigate the difference between the mean and variability of anterior pelvic tilt angles in each subject group. Each sample group comprised of 17 subjects. Elite cyclist were members of the Australian Institute of Sport Track Cycling Squad. Non-cyclists were within 12 months of age, of the same gender and the same race as their elite cyclist pair. Anterior pelvic tilt angles were measured with the SmartLevel ® sensor module, which is essentially a digital electronic inclinometer. Angular measurements were obtained from a long sitting position in order to gain an end of range value for anterior pelvic tilt. High intraclass correlation coefficents (ICC 1,1) were obtained from the measurement tool, intra-examiner and inter-examiner reliability trials. Anterior pelvic tilt angles for elite cyclists ranged from +3.4° to +22.4° with a mean of +12.17°. Anterior pelvic tilt angles for non-cyclists ranged from -20.8° to +11.4° with a mean of -5.29°. The results of this study found mean anterior pelvic tilt to be significantly greater (p < 0.01) in elite cyclists when compared to non-cyclists. Variability was found to be significantly greater (p < 0.05) in the non-cyclist group. This study has concluded that large angles of anterior pelvic tilt are a sport specific quality of elite cyclists. Cyclists competing at any level can be screened to gain a baseline measure of anterior pelvic tilt. Limiting factors to this movement need to be determined on an individual basis so that cyclists aiming to optimise performance can undertake specific training programs to enhance this variable.